Bad Habits, or, Can Reflexivity Be Good Again?. (April 2020) - Rangan, Pooja
Abstract : In her response to the forum on Immediations: The Humanitarian Impulse in Documentary (Duke University Press, 2017), author Pooja Rangan takes up a range of issues that emerge in responses to her book by Rey Chow, Lucas Hilderbrand, Ragini Tharoor Srinivasan, and Naomi Waltham-Smith. Rangan's response revolves around the question: Has reflexivity become untimely? What is the role of reflexive critique in a time of existential crisis? In answering this question, Rangan argues that alongside a "non-naive commitment to a notion of the truth" (a topic that emerges in several of the responses as well as in recent literature on documentary), documentary scholars must pursue a radically uncynical commitment to reflexivity. Redefining reflexivity as a form of "restoration work" (Eli Clare) or "wake work" (Christina Sharpe), Rangan traces the shared investments of documentary critique and contemporary analyses of disability and Black existence.